+0

# HELP!!

0
2396
1

8[7 - (6x - 6)] + 6x = 0.

Guest Jun 13, 2017

#1
+4172
+2

8[7 - (6x - 6)] + 6x  =  0          Distribute the   -1   to each term in   (6x - 6)  .

8[7 - 6x + 6] + 6x  =  0           Distribute the   8     to each term in   [7 - 6x + 6]  .

56 - 48x + 48 + 6x  =  0         Combine like terms.

104 - 42x  =  0                       Subtract   104  from both sides of the equation.

- 42x  =  - 104                        Divide both sides of the equation by   -42  .

x  =  52 / 21

x  ≈  2.476

hectictar  Jun 14, 2017
Sort:

#1
+4172
+2

8[7 - (6x - 6)] + 6x  =  0          Distribute the   -1   to each term in   (6x - 6)  .

8[7 - 6x + 6] + 6x  =  0           Distribute the   8     to each term in   [7 - 6x + 6]  .

56 - 48x + 48 + 6x  =  0         Combine like terms.

104 - 42x  =  0                       Subtract   104  from both sides of the equation.

- 42x  =  - 104                        Divide both sides of the equation by   -42  .

x  =  52 / 21

x  ≈  2.476

hectictar  Jun 14, 2017

### 7 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details